Relating Personality Traits as Predictors of Work-Family Conflict among Hospital Workforce - Akpunne, Bede Chinonye; Uzonwanne, Francis C.; Ogunsemi, Joshua Oludare; Olusa, Abayomi Olubanjo (International Journal of Innovative Research in Medical Science, 2020)
The work pressure of health personnel has remained a challenge ravaging the efficiency of their indispensable roles in saving other lives and their satisfaction with the management of their own family lives. This study related possible linkages between personality traits and work family conflicts among health personnel. A cross sectional survey design was adopted and 260 (male 116 (44.4%) and female 144 (55.6%)) from six state owned hospitals were randomly selected to participate in this study. They responded to Big Five Inventory (BFI) and Work Family Conflict Scale, both of which are standardized instruments. Four hypotheses were tested and the structural equation model (SEM) with AMOS 26 results revealed a significant positive relationship between work-family conflict and neuroticism. Work-family conflict was negatively linked with openness and agreeableness. Neuroticism (β = 0.320, CR = 5.355, p < 0.001) and openness (β = -0.125, CR = -2.111, p < 0.05) significantly predicted work-family conflict positively and negatively respectively. All the personality traits jointly explained 12% variance in work-family conflict. Age was not found to significantly predict work-family conflict. SPSS 23 results showed a statistically significant reliable difference between the mean scores of the work-family conflict of doctors compared with nurses [t (258) = 2.58, p < .05]. The implications of the findings are discussed in line with family focused hospital management policies.